Pemanfaatan Limbah Industri Baja sebagai Bahan Baku Pembuatan Logam Pig Iron : Peleburan Mill Scale Menggunakan Submerged Arc Furnace [Utilization of Steel Making Industrial Waste to Produce Pig Iron: Smelting Process of Mill Scale Using Submerged Arc...] - Fajar Nurjaman; Nurbaity Marsas Prilitasari; Arif Eko Prasetyo; Eko Nugroho (National Research and Innovation Agency (BRIN), 2019)
Mill scale is a by-product that resulted from the steel making industries containing iron oxides, such as hematite (Fe2O3), magnetite (Fe3O4) and wustite (FeO). The smelting process of mill scale into pig iron as secondary raw material for the steel making process has conducted. A 30 Kg of mill scale which crushed into -40 mesh, 0-6 kg amount of coal (internal reductant) and 2 wt.% (0.6 kg) of bentonite (binder) were mixed homogeneously and agglomerated using briquette machine. The composite briquette had been smelting together with 7-8 kg of coke (external reductant) and 0-4.5 kg of limestone (flux) using submerged arc furnace. The smelting process was carried out for 45 minutes, and the pouring temperature was 1450-1500 ºC. The study of coal addition in composite briquette, amount of cokes and limestone addition in the smelting process of mill scale has been investigated clearly. The optimum specified consumption energy of smelting process of mill scale was 3.64 kWh/kg product, resulted from the smelting of 30 kg of mill scale with 0% coal addition in composite briquette together with 3 kg (10 wt.%) lime stones and 7 kg of cokes (stoichiometric) addition. The optimum basicity for smelting a mill scale was 1.0. The pig iron which resulted from smelting the mill scale could promote as a raw material for producing grey cast iron, white cast iron, and malleable cast iron. AbstrakMill scale merupakan limbah/produk samping dari industri baja yang mengandung senyawa besi oksida hematite (Fe2O3), magnetite (Fe3O4) dan wustite (FeO). Telah dilakukan proses peleburan mill scale menjadi logam pig iron sebagai bahan baku alternatif untuk pembuatan material baja. Sebanyak 30 kg mill scale digerus hingga berukuran -40 mesh, kemudian dilakukan proses pencampuran dengan menambahkan batubara (reduktor internal) dan bentonite (perekat) sebanyak 2% berat untuk selanjutnya dilakukan proses aglomerasi menggunakan mesin briket. Briket komposit mill scale dilebur bersama dengan kokas (reduktor eksternal) dan batu kapur (material fluks) menggunakan submerged arc furnace. Pengaruh penambahan batubara dalam briket komposit, jumlah kokas dan batu kapur dalam proses peleburan mill scale telah dipelajari. Dari proses peleburan mill scale diperoleh kondisi optimum, yaitu konsumsi energi spesifik sebesar 3,64 kWH/kg produk, dengan menggunakan briket komposit mill scale dengan penambahan 0% batubara dan penambahan batu kapur sebanyak 3 kg (10% berat) serta kokas sebanyak 7 kg (stoikiometri). Basisitas optimum proses peleburan mill scale adalah 1,0. Produk logam pig iron hasil peleburan mill scale dapat dikembangkan lebih lanjut sebagai bahan baku pembuatan material besi tuang kelabu, putih dan mampu tempa.